Frequency of Interstitial Nephritis in Patients Taking Proton Pump Inhibitor - Manzoor , Rida; Fazal Ur Rehman; Javeria; Nadia; Shah , Syed Nadir; Inamullah; Khushal; Kakar , Sana Ullah (Indus Journal of Bioscience Research, 2025)
Background: Acute interstitial nephritis (AIN), a major cause of drug-induced acute kidney injury (AKI) and possible chronic kidney disease (CKD) is linked to extended PPI use. Proton pump inhibitors (PPIs) are frequently recommended for acid-related gastrointestinal illnesses. At a tertiary care hospital in Quetta, Pakistan, this study examines the incidence and clinical consequences of PPI-induced interstitial nephritis in patients on long-term PPI therapy. Methods: One hundred individuals with a clinical and laboratory diagnosis of interstitial nephritis who had been using PPIs for at least six months were included in this qualitative analysis. Reviews of medical records, reports from kidney biopsies, and semi-structured interviews with patients and nephrologists were used to gather data. Laboratory parameters, histopathological results, demographics, and symptoms were all examined using descriptive statistics. Results: Of the participants, 80% had been taking PPIs for more than a year, and 40% had been taking them for more than three years. AKI (60%), decreased urine production (55%), and weariness (70%), were common symptoms. Laboratory results showed a lower estimated glomerular filtration rate (eGFR) (45 ± 12 mL/min/1.73m²) and an increased serum creatinine (2.1 ± 0.5 mg/dL). The diagnosis of AIN was supported by renal biopsies, which showed eosinophilic infiltration in 60% of cases and tubulointerstitial inflammation in 85% of cases. Fibrosis was observed in 30% of cases, indicating CKD progression risk. Conclusion: This study emphasizes the significance of routine renal function monitoring by demonstrating a substantial association between long-term PPI usage and interstitial nephritis. Renal outcomes can be improved and the risk of CKD decreased with early identification and prompt PPI discontinuation. Safer prescribing procedures should be used by medical professionals to lessen nephrotoxic consequences.